Improvement Tax Literacy in Academic Activities Abroad - Deden Tarmidi; Lin Oktris; Abdul Hadi Zulkafli; Laila Meiliyandrie Indah Wardanie; Desti Silvia; Nazwa Lilayeniva (EQUATOR SINAR AKADEMIA, 2026)
Urbanisation and globalisation have occurred in recent years, with the movement of products and human resources between countries increasing rapidly, including academic activities between countries. Teachers, lecturers, researchers and even students have blurred national boundaries in the process of seeking and sharing knowledge, including the benefits that come with it. In domestic tax regulations and international tax treaties, benefits for academic activities are specifically reviewed, but not all academics who are also taxpayers understand and are aware of this, so this international collaborative community service activity is important to increase academics' understanding of tax regulations related to the benefits of these academic activities. Universiti Sains Malaysia is a partner in this activity, with academic resources and experience as a manager, recipient, and provider in academic activities such as seminars, exchange lectures, exchange students, and scholarships for overseas students. This activity aims to and is expected to increase taxpayers' understanding, especially academics, of tax regulations on benefits in academic activities between countries. This event was held at Universitas Mercu Buana in April 2026 for dozens of vocational school teachers specialising in accounting who are members of the Tangerang City Accounting Teachers’ Working Group. According to the questionnaire and the participants’ feedback, information regarding tax matters relating to academic income has now been received and is a matter of concern for every participant, thereby encouraging tax compliance and helping to avoid tax penalties in the future.